APLIKASI ENKRIPSI DAN DEKRIPSI DATA MENGGUNAKAN TINY ENCRYPTION ALGORITHM (TEA) BERBASIS JAVA - Liana Liana; Sutardi Sutardi; Nur Fajriah Muchlis (semanTIK, 2018)
The need for data security is increasing along with the development of digital technology. Almost all communication and transaction activities are now done digitally so that worries about missing data will increase. Data is very important, so accuracy and precision of data is needed in the decision-making process. The importance of the value of a data causes the availability of data security, therefore data falls precisely and accurately to the right partyIn this study designed a data security application. Encryption method is used to secure data by applying algorithm of Tiny Encryption Algorithm (TEA). In the encryption process performed 16 rounds where each round consists of; additions, key substitutions, and data, and XOR.The results of the study built a data security application that can secure data by applying the algorithm Tiny Encryption Algorithm (TEA). From the test results prove that application is able to secure extension txt and docx. The larger the size of the encrypted data the more time it takes for the encryption process. Keywords— Data, TEA, Encryption, Decryption DOI : 10.5281/zenodo.1402400